Implementasi Nilai-Nilai Profetik Melalui Program Semangat Subuh Di SMK Muhammadiyah Kajen - Safinatunaja, Dhifa; Jamilah, Elok Indah; Salsabila, Bintang; Syafruddin, Adnan; Darutama, Ardiyan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The purpose of Islamic education is the containment of certain values that view the Islamic religion which in its realization is realized by having an Islamic personality who believes and fears God Almighty, has a noble, healthy, and knowledgeable nature. This is contrary to the current reality of moral degradation so that educational institutions need to strive to live prophetic values through building a school culture based on these prophetic values. In the process of collecting data, the author made observations and interviews with related parties. This research uses qualitative methods as research methods. Based on the results of research conducted by researchers at SMK Muhammadiyah Kajen, that SMK Muhammadiyah Kajen has a school culture called the Spirit of Subuh. The Spirit of Subuh program at SMK Muhammadiyah Kajen is an implementation of prophetic values in everyday life. The congregational Fajr Spirit Movement has a noble goal, which is to get used to a healthy life spiritually and physically. The choice of dawn time was chosen because at that time we have the best energy. Through this program, the school wants to shape the Islamic character of its students. One of the methods chosen is through morning prayers performed in congregation. The Semangat Subuh program is also one of the efforts to realize the school's vision, which is to produce Islamic, competent, and outstanding graduates. This concept of example is found in the Qur'an Surah Al-Ahzab verse 21 Therefore, the teacher as the successor of the struggle of the Prophet should be an example for his students. Exemplary and habituation in education is one of the important factors that can determine success in prophetic values.